Prader-Willi syndrome due to an unbalanced de novo translocation [t(15;19)(q12;p13.3)] - Dang, Vy (Cytogenet Genome Res, 2016)
BACKGROUND AND AIMS: Prader-Willi syndrome (PWS) is a complex, multisystem genetic disorder characterized by endocrine, neurologic and behavioral abnormalities. We report the first case of an unbalanced de-novo reciprocal translocation of chromosome 15 and 19: 45,XY,-15, der (19)t(15;19)(q12;p13.3) resulting in monosomy for the PWS chromosome critical region. We performed high resolution SNP microarray to characterize the breakpoints. CASE REPORT: Our patient had several typical features for PWS including infantile hypotonia, a poor suck and feeding difficulties, tantrums, skin picking, compulsions, small hands and feet and food seeking but not hypopigmentation, a micropenis, cryptorchidism or obesity as common findings seen in PWS at the time of examination at 6 years of age. He had seizures noted from 1 to 3 years of age and marked cognitive delay. RESULTS: High resolution SNP microarray analysis identified an atypical PWS Type I deletion of chromosome 15 involving proximal breakpoint BP1. The deletion extended beyond the GABRB3 gene but was proximal to the usual distal breakpoint (BP3) within the 15q11-q13 region and GABRA5, GABRG3 and OCA2 genes were intact. CONCLUSION: We report a case with atypical features for PWS associated with an unbalanced de-novo reciprocal translocation resulting in monosomy for the 15q11.1–15q12 with intact GABRA5, GABRG3 and OCA2 genes. No deletion of 19p13.3 band was detected therefore the patient was not at an increased risk of tumors from Peutz-Jeghers syndrome associated with a deletion of the STK11 gene.